Answer:
c
Step-by-step explanation:
It is two units shifted downwards. you can see it by substituting x=0 for both equations
Answer:
x = 3
Step-by-step explanation:
(x - 1)2 = 4
how to get this solved is very simple.
first step to apply is the BODMAS RULE
B..................... bracket
O..................... of
D.....................Division
M.................... multiplication
A..................... addition
S.................... Subtraction
so (x - 1)2 = 4
we have,
2x - 2 = 4 ( by opening the bracket)
collect the like terms
2x = 4+2
divide both sides by 2
2x/2 = 6/2
x = 3
to check if your answer is correct put the value of x = 3 into the question and see if the right hand side will equal to the left handside
(x - 1)2 = 4
(3-1)2=4
2(2)=4
4=4.............................. proved
Answer:
8cm and 9cm
Step-by-step explanation:
8cm and 9cm would be the two possible lengths for the triangle because for the triangle to work you need the other two other sides when added together needs to be greater then 13. Furthermore 5 + 8 = 13 and as 13 is the same length as the one side that is given, a triangle couldn't possibly be formed as it would just be a straight line. Moreover, this is the same with 6 + 7 which is also 13. 7 + 2 is 9 and because 9<13 a triangle couldn't possibly be formed. Finally, 8 + 9 which equals to 17 are the only two possible lengths for the triangle as 17 > 12.